Molecular recognition of an acyl–enzyme intermediate on the lipase B from Candida antarctica - Toledo, Victoria; Llerena Suster, Carlos Rafael; Ferreira, María Luján; Collins, Sebastián Enrique; Briand, Laura Estefania (Catalysis Science & Technology)
This investigation provides evidence of the acyl enzyme species involved in the interaction of R/S-ketoprofen with the lipase B from Candida antarctica. The interaction between the profen and the enzyme was studied by in situ time-resolved ATR-FTIR under both static and transient conditions. Particularly, modulation excitation spectroscopy (MES) with phase sensitive detection (PSD) allowed us to univocally distinguish the signals belonging to the interaction between ketoprofen and the enzyme from the strong background signals. These experimental tools coupled with theoretical DFT analysis allowed us to propose various species derived from the interaction of ketoprofen with serine through H bonding (without reaction) and the acyl enzyme species (ester bond formation) which are the intermediates in the biocatalytic assisted esterification and hydrolysis using lipases. Fil: Toledo, Victoria. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata. Centro de Investigación y Desarrollo en Ciencias Aplicadas Argentina Fil: Llerena Suster, Carlos Rafael. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata. Centro de Investigación y Desarrollo en Ciencias Aplicadas Argentina Fil: Ferreira, María Luján. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Bahía Blanca. Planta Piloto de Ingeniería Química. Universidad Nacional del Sur. Planta Piloto de Ingeniería Química; Argentina Fil: Collins, Sebastián Enrique. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Santa Fe. Instituto de Desarrollo Tecnológico para la Industria Química. Universidad Nacional del Litoral. Instituto de Desarrollo Tecnológico para la Industria Química; Argentina Fil: Briand, Laura Estefania. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata. Centro de Investigación y ...